Application of the Demonstration Method to Improve Concept Understanding and Learning Activities of Students in Physics Subjects - Simun Ozuho; Sehou Zhadiq; Iwuela Tharem (Newinera Publisher, 2021)
Using the demonstration technique in conjunction with physics instruction, the purpose of this research is to improve students' comprehension of their ideas. Classroom action research is used in this study, and it is divided into two cycles, with each cycle consisting of six sessions each cycle. It is necessary to prepare ahead, take activities, observe and reflect as part of the research process. Based on the findings, students' comprehension of physics topics improved when they were taught using the demonstrative approach. Cycle I students' understanding score averaged 67 points with a standard deviation of 14.92, while the second cycle students' understanding score averaged 79 points with a standard deviation of 9.84. Students' understanding score increased in both cycles I and II, with the average value of 67 points and the standard deviation of 14.92. On the basis of the study's findings, it is possible to infer that the use of physics learning using the demonstration technique has improved students' comprehension of topics in physics